An attempt to separate cimmerian culture from the cimmerian-scythian cultural community penetrated into the Armenian Highland (On Archaeological Data) - Tumanyan, Garegin (History and Culture, 2025)
Because of the unity of Cimmerian and Scythian cultures, separating Cimmerian culture from the Cimmerian-Scythian cultural community is difficult. Yet, the similarity of these cultures is morphological rather than typological, meaning that these tribal groups share the same economical-cultural type but represent different archaeological cultures. Specifically, Cimmerian culture lacks a constituent of the “Scythian triad” – beast style. Instead, a geometrical ornament, especially, rhombus inscribed into circle is typical for Cimmerian culture. The specificities of Cimmerian and Scythian funereal constructions, funerary sculptures, and funerary rituals (particularly, skeleton positions) are discussed. Differences were observed in weapon sets and horse trappings. So far, the study identified 57 sepulchres belonging to 14 graveyards, 5 “other” graveyards, and 9 settlements that have the needed quantity of characteristics/items typical for Cimmerian culture. An inference could be made that Shirak Plateau was one of the main regions where Cimmerians were settled, where from they could penetrate into the western part of Aragatsotn province. Their trace is also detected in the West of the Armenian Highland – in provinces Bardzr Hayk, Tsopk and Aghdznik. Presumably, a considerable mass of Cimmerian tribes settled next to the Minor Armenia – in Gamirk, where from they moved to the North and West.
Keywords: Armenian Highland; Cimmerian; characteristic; typical; sepulchre; settlement; archaeological culture; stele